Unbridling the Tongues of Women: a biography of Catherine Helen Spence - Magarey, Susan (University of Adelaide Press, 2010)
Originally published in 1985, this revised edition with an updated Introduction, is being published by the University of Adelaide Press to commemorate the anniversary of Catherine Helen Spence's death on 3 April 1910. Catherine Helen Spence was a charismatic public speaker in the late nineteenth century, a time when women were supposed to speak only at their own firesides. In challenging the custom and convention that confined middle-class women to the domestic sphere, she was carving a new path into the world of public politics along which other women would follow, in the first Australian colony to win votes for women. She was also much more -- a novelist deserving comparison with George Eliot, Elizabeth Gaskell, and Charlotte Perkins Gilman; a pioneering woman journalist; a 'public intellectual' a century before the term was coined; a philanthropic innovator in social welfare and education, with an influence reaching far beyond South Australia; Australia's first female political candidate. A 'New Woman', she declared herself. The 'Grand Old Woman of Australia' others called her.